CircBACH1/let-7a-5p axis enhances the proliferation and metastasis of colorectal cancer by upregulating CREB5 expression - Li, Jutang (J Gastrointest Oncol, 2020)
BACKGROUND: In this study, we investigated the influences of circBACH1 on the proliferation, metastasis, migration, and apoptosis of human colorectal cancer LoVo cells and explored the molecular mechanism of its effect to guide the clinical diagnosis, treatment, and follow-up of colorectal cancer. METHODS: The expression of circBACH1 in colorectal cancer cells was measured to determine the high expression of BACH1 in colorectal cancer (CRC). LoVo was selected for a follow-up experiment. Then, quantificational reverse transcription-polymerase chain reaction (qRT-PCR) and biotinylated let-7a-5p probes were used to confirm that the expression of let-7a-5p was lowered in colorectal cancer, and let-7a-5p was the downstream target of BACH1 in CRC. Cell counting Kit-8 (CCK-8), Transwell, and wound repair experiments confirmed that BACH1 augmented the proliferation, migration, and metastasis of CRC by regulating let-7a-5p. The apoptosis rate was measured by flow cytometry. It was concluded that BACH1 inhibited apoptosis by regulating let-7a-5p in CRC. The results of the bioinformatics analysis showed that CREB5 was overexpressed in CRC by qRT-PCR and Western blot. The results of qRT-PCR, CCK-8 assay, Transwell assay, and flow cytometry showed that let-7a-5p inhibited the proliferation, migration, and invasion of CRC cells through targeting CREB5 and augmented cell apoptosis. According to tumor growth and the determination of CREB5 by Western blot, BACH1 can affect the proliferation of CRC cells through CREB5. RESULTS: Overall, our study confirmed that BACH1 and CREB5 increased, while the expression of let-7a-5p was lowered in colorectal cancer cells. These different expressions enhance the proliferation, metastasis, and migration of colorectal cancer cells and inhibit colorectal cancer cells’ apoptosis. CONCLUSIONS: Our study clearly illustrates the molecular mechanism of circBACH1 acting on colorectal cancer, which can be used as a therapeutic target to augment colorectal cancer treatment.